Estimated download highs in the micro basin Huaycoloro (Huachipa-Lima) - Romero, Armando (2010)
The microbasin is a basin Huaycoloro very dynamic, with various phenomena of landslides in recent decades has caused landslides and flooding avenue in the bottom of the basin, causing great economic losses, especially in populations HuachipaCampoy and Zarate. In this first paper we estimate peak discharges for which begins with a geographical description of the study area, then the hydrologic analysis is done and finally get the estimation of peak discharges for the synthetic unit method (SCS), resulting the following maximum capacities for 10 years 18.36 m3 / s to 50.40 m3 / s and finally 50 years to 200 years 116.91 m3 / s.